1997
DOI: 10.1038/sj.onc.1201154
|View full text |Cite
|
Sign up to set email alerts
|

Frequent loss of heterozygosity on chromosome 10q in muscle-invasive transitional cell carcinomas of the bladder

Abstract: Loss of heterozygosity (LOH) on chromosome 10 has been observed in several human cancers including glioblastomas, meningiomas, melanomas and endometrial and prostate carcinomas. We have investigated the incidence of LOH on chromosome 10 in 36 human transitional cell carcinomas (TCCs) of the bladder, three upper urinary tract TCCs and one lymph node metastasis, using a panel of 27 highly polymorphic markers spanning 10p (short arm) and 10q (long arm). Fourteen bladder tumours (39%), the three upper urinary trac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
74
0
3

Year Published

1998
1998
2004
2004

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(81 citation statements)
references
References 21 publications
4
74
0
3
Order By: Relevance
“…In addition, numerous studies of other human tumour types have suggested multiple tumour suppressor loci may be found on 10q. The predicted regions include 10q24-qter in glioblastoma multiforme (Albarosa et al, 1996;Rasheed et al, 1995), 10q23-q26 in endometrial cancer (Pei er et al, 1995), 10q21-q23 in renal cell carcinoma (Morita et al, 1991), 10q22-qter in malignant melanoma (Herbst et al, 1994), 10qter in hepatocellular carcinoma (Fujimori et al, 1991) and 10q24.1-q24.3 and 10q26.1-q26.2 in muscle-invasive bladder cancers (Cappellen et al, 1997). Each of these regions crosses the predicted SROs described in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, numerous studies of other human tumour types have suggested multiple tumour suppressor loci may be found on 10q. The predicted regions include 10q24-qter in glioblastoma multiforme (Albarosa et al, 1996;Rasheed et al, 1995), 10q23-q26 in endometrial cancer (Pei er et al, 1995), 10q21-q23 in renal cell carcinoma (Morita et al, 1991), 10q22-qter in malignant melanoma (Herbst et al, 1994), 10qter in hepatocellular carcinoma (Fujimori et al, 1991) and 10q24.1-q24.3 and 10q26.1-q26.2 in muscle-invasive bladder cancers (Cappellen et al, 1997). Each of these regions crosses the predicted SROs described in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of such mutations in these tumours could re¯ect the fact that PTEN inactivation is a very late event in tumorigenesis and thus, mutations are only observed in advanced stage tumours or cell lines. Alternatively, it is possible that PTEN does not represent the only or even the major tumour suppressor gene on 10q23, a possibility consistent with the ®nding of multiple distinct regions of allele loss on 10q in a variety of human tumours (Albarosa et al, 1996;Cappellen et al, 1997;Gray et al, 1996;Ittmann, 1996).…”
Section: Introductionmentioning
confidence: 88%
“…The 10 remaining CIS were obtained from patients diagnosed at the Rotterdam University Hospital (Rotterdam, The Netherlands). DNA from pTa and pT1-4 tumors was extracted from samples frozen immediately in liquid nitrogen as previously described 20 or from formalin-fixed, paraffinembedded tissue, using the tissue DNA extraction kit from Qiagen (Courtaboeuf, France). All samples retained for this analysis contained more than 80% tumor cells, as assessed by histological examination.…”
Section: Tumor Samplesmentioning
confidence: 99%
“…Little is known about the genetic alterations associated with the metastatic phenotype. Deletions of the long arm of chromosome 10 have been reported in many types of tumour, including colorectal carcinomas (Frayling et al, 1997), and are correlated with tumour progression and/or metastasis formation in several of these cancers, such as glial tumours (Balesaria et al, 1999), lung cancer (Petersen et al, 1998), head and neck squamous cell carcinomas (Bockmuhl et al, 2002), bladder (Cappellen et al, 1997), prostate (Komiya et al, 1996) and breast carcinomas (Bose et al, 1998). Several putative or known tumour-suppressor genes have been mapped to 10q, including BMPR1A on 10q23.2 and PTEN/MMAC1/TEP1 on 10q23.3.…”
mentioning
confidence: 99%